A system for supporting the selection of hold baggage screening organization option at the airport - Jacek SKORUPSKI; Piotr UCHROŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
Checked baggage, placed in the hold of an aircraft, screening is one of the most important elements of the airport security system, affecting the safety of entire air transport. In various airports, technical equipment but also the organization of checked baggage screening process vary widely. The paper presents an analysis aimed at creating a model of the organization of the screening process. Using this model can help airport managers in selection of the variant of screening organization depending on the current situation in the terminal. The essence of the method is to determine the relationship between factors such as: technical equipment, staff training and the number of staff errors, and also a variant of the organization of screening process and the effectiveness of the screening. This relationship cannot be defined in a precise and accurate manner, so it is necessary to use methods appropriate for the case when we have the information imprecise, uncertain and subjective. The obtained results allow to assess how effective is the checked baggage screening process at each of the possible variants of the organization. This allows the selection of a variant according to the technical equipment we have and also what passengers stream must be serviced.